The Influence of Indonesian Language Learning Methods Viewed from the Aspect of Learning Media Usage Class X Students of SMK Pratidina Makassar - Saleh. S, Muh. (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This study aims to find effective learning solutions and solve problems by developing teaching methods that are used to achieve meaningful learning objectives. The selection of teaching methods is a procedure, sequence, steps, and approach used by educators in designing the achievement of learning goals. The selection of methods and the use of Indonesian language learning models, such as the grammar-translation method, the direct method, and the audiolingual method, demonstrate a dominant characteristic. The use of Indonesian language teaching methods is a